2016
DOI: 10.3109/1354750x.2016.1171904
|View full text |Cite
|
Sign up to set email alerts
|

LINE-1 and inflammatory gene methylation levels are early biomarkers of metabolic changes: association with adiposity

Abstract: We analyzed whether global and inflammatory genes methylation can be early predictors of metabolic changes and their associations with the diet, in a cross-sectional study (n = 40). Higher global methylation was associated to adiposity, insulin resistance, and lower quality of the diet. Methylation of IL-6, SERPINE1 and CRP genes was related to adiposity traits and macronutrients intake. SERPINE1 hypermethylation was also related to some metabolic alterations. CRP methylation was a better predictor of insulin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 56 publications
0
14
0
Order By: Relevance
“…Because of its high representation throughout the genome, LINE-1 methylation has been shown to correlate with global genomic DNA methylation content [50], and is regarded as a measure of global DNA methylation [51]. Some investigations have linked changes in LINE-1 methylation to inflammation [52,53]. Lower LINE-1 methylation was associated with higher serum vascular Cell Adhesion Molecule-1 [54], which has been identified as an independent marker of cardiovascular disease [55].…”
Section: Discussionmentioning
confidence: 99%
“…Because of its high representation throughout the genome, LINE-1 methylation has been shown to correlate with global genomic DNA methylation content [50], and is regarded as a measure of global DNA methylation [51]. Some investigations have linked changes in LINE-1 methylation to inflammation [52,53]. Lower LINE-1 methylation was associated with higher serum vascular Cell Adhesion Molecule-1 [54], which has been identified as an independent marker of cardiovascular disease [55].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the subjects in the Samoan study had a substantially higher BMI than our study subjects and the NTFS study subjects. Recent reports indicate that alterations in DNA methylation are closely associated with obesity 24 , 25 ) . The Multi-Ethnic Study of Atherosclerosis (MESA) reported that individuals with high BMI (≥ 40 kg/m 2 ) had higher LINE-1 DNA methylation levels in leukocytes than those with normal BMI (< 25 kg/m 2 ) in a cohort of 987 individuals aged 45–84 years 26 ) .…”
Section: Discussionmentioning
confidence: 99%
“…Global and gene-specific DNA methylation alterations, which vary with age, sex and socioeconomic status, may also be predictive biomarkers of weight loss response to intervention programs ( 91 ). Global DNA methylation and inflammatory gene promoter hypermethylation are reported to be early biomarkers of adiposity and metabolic alterations ( 93 ). Global DNA methylation and hydroxymethylation may functions as biomarkers in obesity and associated comorbidities.…”
Section: Discussionmentioning
confidence: 99%